Logged labour: a new paradigm of work organisation?. (1st April 2016) - ,
Abstract : This essay argues that, during the period following the financial crisis of 2007–8, several different trends, already visible in earlier periods, have converged to create a new pattern of work organisation, a pattern which is now approaching critical mass. Across all sectors of the economy, primary, secondary or tertiary, whether previously classified as public or private, formal or informal, manual or white-collar, high-skilled or low-skilled, this emerging model of work introduces a range of common features whose combined impact is large enough to justify the proposition that a new paradigm of work is in creation, perhaps representing the final dissolution of the normative model that emerged in developed economies in the third quarter of the twentieth century. In this new model, workers are increasingly managed via online platforms, monitored indirectly and expected to produce measurable outcomes. Their work is 'logged' in three distinct senses: it is cut up into standard, quantifiable components; it is subjected to continuous surveillance and monitoring; and it requires the worker to be connected to an online platform in order to obtain work. In a curious paradox, work is increasingly formalised even while it becomes less predictable and more precarious, with workers having to resubmit themselves repeatedly for employment, funding, promotion or inclusion in a particular team, and required to respond at short notice to unpredictable demands for work. The ramifications of this development are huge, since it creates major mismatches between the realities of the labour market and other aspects of social and economic life, including welfare systems, labour and consumer regulation and time regimes. The article draws on a large body of past work by the author on work organisation restructuring as well as current research on online labour platforms.